Factors Associated with Medication Adherence among hypertensive Patients in a Tertiary Health Center: A Cross-Sectional Study - BA, Ezeala-Adikaibe; N, Mbadiwe; G, Okudo; N, Nwosu; N, Nwobodo; G, Onyebueke; M, Nwobodo; T, Nnaji; UH, Okafor; C, Orjioke; T, Okpara; E, Aneke; et al. (Archives of Community Medicine and Public Health, 2017)
Introduction: Medication non-adherence is a major hindrance in the treatment of hypertension in Sub Saharan Africa. It is a major modifiable contributor to poor blood pressure control and complications of the disorder. An understanding of the factors that are associated with drug adherence in hypertension will contribute positively to the overall planning of public health educational programs on hypertension. Methods: This study was cross sectional and descriptive in nature conducted in the medical outpatient clinic of Enugu State University Teaching Hospital, Enugu Nigeria. Data collection was done using a semi-structured questionnaire. The Morinsky-Green Medication adherence scale was used to estimate medication adherence. Statistical analyses was done using SPSS version 22 (IBM Corporation, New York, USA). Results: A total of 436 patients were surveyed in this study. Most of the patients (90.1%) sometimes forget to take their medications or do not bring their medications along when they leave home (94.3%). The highest rates of non-adherence were reported in patients who were totally dependent (62.5%). High depression scores, low disability scores and the presence of peptic ulcer disease correlated with non-adherence. In regression analysis Morinsky-Green scores (R2 = 0.04), decreased by a factor of 0.06 with a unit increase in level of dependence, by a factor of 0.09 with a unit increase in HADS depression scores and by 0.73 in those that have peptic ulcer. Conclusions:Non-adherence is high among hypertensive patients attending tertiary care centers in the South East. Educational measures targeted towards improving adherence are needed to reduce the level of non-adherence.